THE STATE AS AN ESSENTIAL VALUE (ḌARŪRIYYĀT) OF THE MAQĀṢID AL-SHARĪ‘AH - Saim Kayadibi (AHKAM : Jurnal Ilmu Syariah, 2019)
Muslim scholars have mainly considered the maqāṣid al-sharī‘ah within three categories: ḍarūriyyāt (the essentials), ḥājiyyāt (the complementaries) and tahsīniyyāt (the desirables or the embellishments). The concept of maṣlaḥah is meant to protect the maqāṣid al-sharī‘ah (the higher objectives of sharī‘ah), which consist of seven essential values, namely religion, life, intellect, lineage, wealth, honour and state, all of which promote the people’s welfare and prevent all kind of evils. They are considered essentials because neglecting them would cause total social disruption and anarchy. Even though classical scholars considered the darūriyyāt to be six in number, this article suggests that the value of “state” be added to this list. The values in the darūriyyāt category must be upheld and protected from any real or unexpected threats either by maintaining the essentials or removing the disruption. The concept of state is just as essential as the other six values, for without it, all of them would be endangered and considered incomplete. Therefore, the “state” value guarantees the continued existence of other values. In this paper, the author argues that this value should be regarded as a seventh essential value. Para cendekiawan Muslim  telah mempertimbangkan maqāṣid al-sharī‘ah dalam tiga kategori: ūarūriyyāt (esensi), ḥājiyyāt (pelengkap) dan tahsīniyyāt (keinginan atau hiasan). Konsep maṣlaḥat dimaksudkan untuk melindungi maqāṣid al-sharī'ah (tujuan yang lebih tinggi dari syariat), yang terdiri dari tujuh nilai esensial, yaitu agama, kehidupan, kecerdasan, garis keturunan, kekayaan, kehormatan dan negara. Semuanya bermaksud kesejahteraan rakyat dan mencegah semua jenis kejahatan. Mengabaikan hal itu akan menyebabkan gangguan sosial dan anarki total. Meskipun para sarjana klasik menganggap darūriyyāt berjumlah enam, penelitian ini menunjukkan bahwa nilai "negara" ditambahkan ke daftar ini. Nilai-nilai dalam kategori itu harus dijunjung tinggi dan dilindungi dari ancaman nyata atau tidak terduga, baik dengan mempertahankan esensi atau menghilangkan gangguan. Konsep negara sama pentingnya dengan enam nilai lainnya, karena tanpa itu, semuanya akan terancam dan dianggap tidak lengkap. Oleh karena itu, nilai “negara” menjamin keberlanjutan keberadaan nilai-nilai lain. Peneliti  berpendapat bahwa nilai ini harus dianggap sebagai nilai esensial ketujuh.